DISTRIBUTION OF DYSFUNCTIONAL DISORDERS OF THE BILIAL TRACT IN CHILDREN AND ADOLESCENTS OF THE KRASNODAR TERRITORY - G. V. Naumenko; V. A. Sashel; A. V. Burlutskaya (Кубанский научный медицинский вестник, 2017)
Aim. To study the prevalence and structure of dysfunctional disorders of the biliary tract (DRBT) in children and adolescents of theKrasnodarTerritory.Materials and methods. To achieve this goal, an analysis was made of the prevalence and incidence of DRBT in children and adolescents who turned to treatment and prophylactic institutions in theKrasnodarTerritory. Data on the health status of children and adolescents were obtained from the annual reports of children's medical and preventive institutions, annual reports of the Department of Medical Statistics of the Ministry of Health of theKrasnodarTerritory. The main group included 3,065 children and 2,415 adolescents who were examined in schools and pre-school establishments in theKrasnodarTerritory.Results. Against the background of an increase in the overall frequency of pathology of the digestive organs, a significant change in their structure was observed in 2028 (37.0%) children. Thus, diseases of the liver, gallbladder and pancreas were diagnosed in 1480 (27.0%) of the number of patients examined, of them 843 (5.5%) were diagnosed with DRBT. In the early age and preschool age, there were 72 (8.5%), primary school age 225 (26.6%), and senior school age 546 (64.8%). The number of boys was 632 (75.0%), girls – 211 (25.0%).Conclusion. Dependence of the structure of DRBT on the age of the child population, the functional state of the biliary tract was established. Primary hyperfunction of HP and biliary type of CO disorder prevail in children of early and preschool age. At school age, the incidence of hypothyroidism increases, and biliary and pancreatic types of CO dysfunction are equally recorded. In children puberty, secondary dysfunctions of the biliary tract are predominant in the form of hypofunction of HP and pancreatic type of CO disorder.